African Canadian leadership: Continuity, transition, and transformation - Kitossa, Tamari; Lawson, Erica; Howard, Philip S. S. (University of Toronto Press, 2019)
Challenging the myth of African Canadian leadership "in crisis," this book opens a broad vista of inquiry into the many and dynamic ways leadership practices occur in Black Canadian communities. Exploring topics including Black women’s contributions to African Canadian communities, the Black Lives Matter movement, Black LGBTQ, HIV/AIDS advocacy, motherhood and grieving, mentoring, and anti-racism, contributors appraise the complex history and contemporary reality of blackness and leadership in Canada. With Canada as a complex site of Black diasporas, contributors offer an account of multiple forms of leadership and suggest that through surveillance and disruption, practices of self-determined Black leadership are incompatible with, and threatening to, White "structures" of power in Canada. As a whole, African Canadian Leadership offers perspectives that are complex, non-aligned, and in critical conversation about class, gender, sexuality, and the politics of African Canadian communities.
Keywords: afro-féminisme; amériques; approches et analyses; canada; cours; discours dominant; fem3300; féminisme afroaméricain; histoire et politique; identités LGBTQIA2+; maternité; militance; premier cycle; racisme; régions géographiques; systèmes d'oppressions; thématiques

Serving each other: Sharing economies and affective labour in montréal's kiki scene - Lundy, Jesse D. (Université Carleton, 2019)
Against a tense socio-political backdrop of white supremacy, intensifying pressures of neoliberal fiscal austerity, and queer necropolitics, this thesis addresses performance-based activist forms of place-making for urban-based queer, trans, and gender nonconforming communities of colour. Using participant observation and qualitative interviews with pioneering members of Montréal’s Kiki scene and Ottawa’s emerging Waacking community and interpreting my findings through the theoretical lens of queer of colour theory, critical whiteness studies, queer Latinx performance studies and Chicana feminism, I argue that Kiki subculture, which is maintained by pedagogical processes of ‘each one, teach one’, is instrumental in facilitating i) life-affirming queer kinship bonds, (ii) alternative ways to simultaneously embody and celebrate nonnormative gender expression with Black, Asian, and Latinx identity, iii) non-capitalist economies of sharing, and iv) hopeful strategies of everyday community activism and resilience to appropriative processes during economic insecurity and necropolitical turmoil.
https://doi.org/10.22215/etd/2020-13975
Keywords: LGBTQIA2+; approches et analyses; discours dominant; ethnologie; identités LGBTQIA2+; militance; montréal; mémoires/thèses; ottawa; queer; queer of color; racisme; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques; étude qualitative; études culturelles